Harnessing Radiation Biology to Augment Immunotherapy for Glioblastoma - Rajani, Karishma R.; Carlstrom, Lucas P.; Parney, Ian F.; Johnson, Aaron J.; Warrington, Arthur E.; Burns, Terry C. (Frontiers in Oncology, 2019)
Glioblastoma is the most common adult primary brain tumor and carries a dismal prognosis. Radiation is a standard first-line therapy, typically deployed following maximal safe surgical debulking when possible, in combination with cytotoxic chemotherapy. For other cancers, standard of care is being transformed by immunotherapies including checkpoint blocking antibodies targeting CTLA-4 and PD-1/PD-L1 frequently yielding long-term remissions. Ongoing studies are evaluating the role of immunotherapy including checkpoint inhibitors for GBM with early generally disappointing results attributed to the immunologically “cold” nature of glioblastoma relative to melanoma and other malignancies successfully treated with immunotherapy. Radiation may serve as a mechanism to improve tumor immunogenicity. In this review, we critically evaluate the current evidence regarding potential to harness radiation as a synergistic facilitator of immunotherapies, through modulation of both the innate and the adaptive immune milieu. Although current preclinical data encourage attempts to harness synergistic biology between radiation and immunotherapy, translation has been slow. Barriers include reluctance to alter current standard of care and radiation and chemotherapy protocols as part of immunotherapy trials, as well as the current paucity of reliable or accessible biomarkers of therapeutic efficacy.